PENINGKATAN USAHA ANEKA OLAHAN UBI DI DESA KENTENG PUNTUKREJO, KECAMATAN NGARGOYOSO, KABUPATEN KARANGANYAR - Asri Nursiwi; Rohula Utami; Edhi Nurhartadi (Jurnal Kewirausahaan dan Bisnis, 2017)
Kenteng Village Puntukrejo is one of the industrial centers ofprocessed sweet potato in Karanganyar Regency. Processed purple sweetpotato products produced include bakpia, wingko, and ice cream.Generally, the problems that occur in the sweet potatoes processing arethe equipment used is not in accordance with the standards for the foodindustry, the limited amount of equipment, hygiene and sanitation duringprocessing is not considered so as to bring the risk of contamination to theend product, as well as stagnant business conditions because the absenceof product diversification and limited marketing area. To solve theproblem through this program of dedication will be done (1) Introductionof appropriate technology for the processing of sweet potato; (2) Trainingof food industry management; (3) Introduction of processing technologyfor 'cassava leaf chips' as an effort to diversify products; (4) IT-basedmarketing training; (5) as well as facilitation of testing of nutrient contenton the end product. Through this dedication activity has been doneIntroduction of processing technology for 'cassava leaf chips' as the effortof product diversification. To improve product quality and productioncapacity has been given the equipment in the form of oven, large capacitymixer, wingko molding, freezer, analytical scales, stainless steel basin, andstainless steel table. Food industry management training in the form ofGood Manufacturing Practices (GMP) training has been given to ensurequality and safe the products. It also provides IT-based marketing trainingto improve product marketing. The results of laboratory analysis, purplesweet potato bakpia has water content 33.29%, mineral content 1.51%, fatcontent 11.91%, protein content 9.34%, carbohydrate content 43.95%, andantioxidant activity 6.20%. Purple sweet potato wingko has water content34.47%, mineral content 1.32%, fat content 11.70%, protein content 3.06%,and carbohydrate content 49.45%. While the cassava leaf chips has watercontent 5.39%, mineral content 5.23%, fat content 32.66%, protein content8.59%, and carbohydrate content 48.13%.Keywords: sweet potato, bakpia sweet potato, wingko sweet potato,cassava leaf chips, Ngargoyoso